2020
DOI: 10.1021/acsaem.9b02052
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Antisolvent Processed Hybrid Metal Halide Perovskites Studied by In Situ Photoluminescence and Its Influence on Optoelectronic Properties

Abstract: The antisolvent dripping time during spin-coating of CH 3 NH 3 PbI 3 (MAPbI 3) strongly impacts film morphology as well as possible formation of the intermediate precursor phase, and-consequently-device performance. Here, we use in situ photoluminescence (PL) to directly monitor the fast-occurring changes during MAPbI 3 synthesis. These measurements reveal how the ideal timing of the antisolvent leads to homogeneous nucleation and pinhole-free films. In addition, these films show significantly reduced nonradia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 54 publications
1
44
0
Order By: Relevance
“…For example, significant attention has been given to the effect that the time of the antisolvent dripping has on perovskite film formation. Through a variety of in and ex situ analysis techniques such as x-ray diffraction (XRD) 15 17 and photoluminescence 18 , 19 , this research has revealed complex, composition-dependent liquid-crystal dynamics and competing crystallization routes that take place during the crucial moments of film formation. Antisolvent–solvent interactions (e.g., dipole–dipole) have been shown to modulate these dynamics 20 , and consequently, strong correlations are observed between antisolvent timing and the resultant film morphology, electronic quality, and photovoltaic performance, highlighting the paramount importance of the antisolvent application step in producing high-quality perovskite films and devices.…”
Section: Introductionmentioning
confidence: 99%
“…For example, significant attention has been given to the effect that the time of the antisolvent dripping has on perovskite film formation. Through a variety of in and ex situ analysis techniques such as x-ray diffraction (XRD) 15 17 and photoluminescence 18 , 19 , this research has revealed complex, composition-dependent liquid-crystal dynamics and competing crystallization routes that take place during the crucial moments of film formation. Antisolvent–solvent interactions (e.g., dipole–dipole) have been shown to modulate these dynamics 20 , and consequently, strong correlations are observed between antisolvent timing and the resultant film morphology, electronic quality, and photovoltaic performance, highlighting the paramount importance of the antisolvent application step in producing high-quality perovskite films and devices.…”
Section: Introductionmentioning
confidence: 99%
“…9 In-depth studies are needed to deconvolve these processes and provide a mechanistic understanding of how nucleation can be promoted and controlled. Possibly, in situ microscopy or PL 138 can provide viable means for such investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, dripping an antisolvent leads to an accelerated crystallization process, induces homogeneous nucleation with high nucleation density, and therefore promotes uniform grain growth. [134][135][136][137][138] The antisolvent process is very successfully used for the preparation of conventional ABX 3 perovskite films. 139,140 The most commonly used antisolvents include toluene, 139 chlorobenzene, 140 and diethyl ether.…”
Section: Solvent Engineeringmentioning
confidence: 99%
“…Many recent in situ studies of halide perovskites have been employed to advance our understanding of dynamical processes related to halide perovskite formation, degradation, ionic movement and phase changes including diffraction measurements, [17]- [22] terahertz spectroscopy, [23]- [25] UV-Vis spectroscopy, [26]- [30] electron microscopy, [31] Raman, [32] and PL. [32]- [40] Frequently, researchers use the terms "light soaking" or "continuous laser irradiation" when a sample is exposed to illumination (typically at fixed power and excitation wavelength) while recording PL or UV-Vis spectra over a certain time. While the term in situ is often used in relation with synthesis.…”
Section: Introductionmentioning
confidence: 99%